Tilikums of Eltteas and Tilikum Drum Corps on courthouse steps, Vancouver, British Columbia, 1912 - Nowell, Frank H.
The Golden Potlatch was a city-wide festival held in July, organized by civic boosters hoping to capitalize on the success of the Alaska-Yukon-Pacific Exposition. The first Golden Potlatch opened in July 1911; the event continued for each of the next three summers before being suspended during wartime. The name reflects the importance of the Klondike gold rush to Seattle and borrows a Chinook jargon term for a gift-giving ceremony. The boosters also used Chinook jargon to call themselves the Tillikums (friend) of Elttaes, (Seattle spelled backward). Thousands of people enjoyed the week-long carnival of parades, aircraft demonstrations and concerts. This photo shows the Tillikums of Eltteas and the Tilikum Drum Corps of Seattle on the steps of the British Columbia Provincial courthouse, now the Vancouver Art Gallery. The group made a trip to Canada to promote Seattle's Golden Potlatch festival. Embossed on front of print: Frank H. Nowell, U.S.A. Photo from album with "Tillikums of Elttaes" embossed on the cover. 1 photographic print: b&w; 9 5/8 x 7 3/4 in.